Development of Android-Based Mobile Learning Media Using Smart App Creator to Improve Students' Multi-Representation Ability in Thermodynamic Materials - Pratiwi, Ildawati Febri; Novita, Nanda; Saifuddin, Saifuddin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research is a development research that aims to determine the feasibility, attractiveness, and convenience of  android-based mobile learning  application products on Thermodynamics material. As well as to find out the increase in the sustainability of multi-percentage of grade XI students in Thermodynamics material with  the mobile learnig  application in learning. This study uses a research and development (R&D)  method with the Borg and Gall model. The methods carried out are tests and questionnaires. Based on the results of data analysis for the expert test, a percentage of 95% was obtained with the criteria of "very feasible". For the validation test, media experts obtained a percentage of 95% with the criteria of "very feasible". As well as the practicality test conducted by physics subject teachers obtained a percentage of 93% with the criterion of "very feasible" and the student response to mobile learning  media obtained a percentage of 79% with the criterion of "interesting and easy".